Psychological Factors of Adolescents Disposition towards Addictive Behavior - Zheleznyakova, YuliyaV. (International Journal of Psychosocial Rehabilitation, 2020)
The problem of loneliness and addictive behavior is one of the most important in modern developmental and pedagogical psychology. In studies of the problem of addictive behavior quite often the attention of scientists focuses on the existing addiction and not enough attention is paid to the prerequisites for addictive behavior development. The influence of parent-child relationships and subjective feelings of loneliness on the formation of addictive behavior in early adolescence are analyzed. The subjective feelings of loneliness of younger adolescents, destructive relationships with parents are ones of the conditions for the emergence of a predisposition to addictive behavior.